Workshop On Optimizing The Use Of Artificial Intelligence (AI) To Increase Lecturers Academic Publications In Reputable International Journals - Yahya, Wachid; Sari, A.Anditha; Susanti, Ratna; Putri, Nawangsih Edynna; Husen, Mohd Nizam (Politeknik Indonusa Surakarta, 2025)
The development of artificial intelligence (AI) technology has had a significant impact on various fields, including learning and research in the academic world. One potential utilization of AI is in supporting the process of writing, editing, and publishing scientific articles in reputable international journals. This article aims to present various AI strategies and applications that can be optimized by academics to improve the quality of learning and productivity of international publications. The method used is a literature study of various scientific articles, industry reports, and trials of several AI platforms commonly used in academia. The stages of activity implementation began with the preparation, implementation and evaluation stages. The results of the activity show that AI has a significant role starting from the reference search stage, literature analysis, manuscript preparation, checking grammar and writing style, to the submission process and selection of suitable journals. AI integration is proven to increase time efficiency, improve manuscript quality, and increase the chances of being accepted by reputable journals. This study recommends the need for training and ethical policies in the use of AI in the academic environment so that its utilization remains in a responsible academic corridor.